Adsorption of nonylphenol on coastal saline soil: Will microplastics play a great role?. (January 2023) - Lu, Jian; Wu, Jie; Wu, Jun; He, Xia
Abstract: Microplastics widely exist in diverse matrices to become important hosts of pollutants. Little information regarding adsorption of emerging contaminants on coastal saline soils influenced by co-existing microplastics is available. Thus, the adsorption behaviors of nonylphenol (NP) on coastal saline soil influenced by microplastics were discussed. Polyvinyl chloride (PVC, 4.7 mm), polyethylene (4.85 mm), and polypropylene (4.51 mm) with addition dose of 10% were used to discuss the effect of microplastic type on adsorption of NP by coastal saline soil while PVC samples with size of 4.7 mm and 0.11 mm were used to explore the effect of microplastic size on NP adsorption. The NP adsorption capacity of the saline soil containing 10% of PVC (4.7 mm) was twice that of soil without PVC. Smaller-size PVC (0.11 mm) with addition amount of 10% enhanced the NP adsorption capacity of the coastal saline soil by 117% to reach 8.91 μg g −1 . The desorption capacity of NP on saline soil decreased from 40% to 30% of total adsorption capacity with co-existing PVC. Adsorption/desorption kinetics of NP on coastal saline soil with PVC microplastics could be well explained by pseudo second order model while Freundlich model could better fit the isotherm data of NP adsorption/desorption to show possible occurrence of the multiple-layer adsorption. This study will provide new information regarding the environmental behaviors of typical emerging contaminants on coastal saline soil containing microplastics. Graphical abstract: Image 1 Highlights: Microplastics significantly increased the adsorption of NP on coastal saline soil. Microplastics decreased the desorption of NP on coastal saline soil. The adsorption capacity of NP on the saline soil containing PVC reached 8.91 μg g −1 Absolute value of ΔG0 increased after microplastics were added in coastal saline soil.